Analysis of Policy for Recovering Losses in State Revenue from Tax Crimes in Indonesia - Jeffery Jeremias; Adiwarman (Dinasti Publisher, 2025)
This study analyzes the policy of state loss recovery in state revenue from tax crimes in Indonesia, focusing on Minister of Finance Regulation (PMK) No. 17 of 2025. Using a qualitative approach with content and narrative analysis from interviews with the Directorate General of Taxes Officials, Academics, and Tax Consultants, this study identifies the urgency of formulating this PMK as a response to previous fragmentation and inefficiency in asset recovery, as well as the increasing complexity of tax crime modus operandi. PMK No. 17 of 2025 is an administrative implementing regulation rooted in the 1945 Constitution, and derives its authority from Laws and Government Regulations, serving to provide necessary technical and operational details. Its formulation process followed a participatory public policy cycle, involving cross-institutional coordination with entities such as the Ministry of Finance, the Attorney General's Office, and the Police, and includes mechanisms for regular evaluation. The policy's implementation adopts a holistic two-pillar approach: preventive through education and compliance improvement, and repressive through law enforcement and asset recovery, with a focus on efficiency and procedural simplification. While the policy design recognizes the importance of inter-agency coordination, operational challenges still require more detailed Standard Operating Procedures (SOP) strengthening. Adaptation to the digital economy and continuous innovation are essential to maintain the policy's future relevance, given the rapid development of crime patterns. Key challenges include consistent coordination, acceleration of legal processes, and enhancement of human resource capacity.